Teologi dan Moralitas dalam Kitab 2 Samuel: Implikasi Etis untuk Masyarakat Modern - Benediktus James Widya Darmaka; Etty Justiana Saragih; Saliim, Frengki; Tamuntuan, Yusuf (LPPM - STT Kadesi Bogor, 2026)
This study examines the theological and moral dimensions of the Book of 2 Samuel by highlighting issues such as sin, repentance, justice, leadership, and its ethical implications for modern society. The aim of this study is to explore how the story of King David, with its moral complexity and the consequences of each of his actions, can serve as a reflective guide in dealing with contemporary ethical challenges. The method used is biblical hermeneutics combined with literature studies to interpret texts in their historical, social, and cultural contexts. This approach allows for a more comprehensive understanding of the theological message of the Book of 2 Samuel and its relevance to life today. The results of the study show that the value of sincere repentance, divine justice, and responsible leadership are universal principles that transcend the context of the times. These values are relevant in responding to modern problems such as abuse of power, integrity crises, and structural corruption. The novelty of this research lies in the effort to reinterpret ancient theological and moral teachings as an applicative ethical framework to strengthen moral leadership and ethical awareness in modern societ